Quality improvement of coconut (Cocos nucifera) milk yogurt analogue. - Zomil, Nica Pearl Solis
Production of yogurt-like product developed by Yap (2014) was modified to improve its microbial quality and sensorial attributes. Results from the coliform test showed that the modified extraction process and pasteurization were efficient in lowering the coliform count of pasteurized coconut milk and destruction of E.coli. The MPN/g of pasteurized coconut milk was within the satisfactory levels for processed products. Triangle test established a significant difference between the two mango-flavored yogurt analogue (F1 − with sweetened Katchamita mango and F2 − with sweetened Carabao mango). F2 which was significantly more preferred (paired-preference test, α = 0.05) was rated like very much. The significantly difference (T-test, α=0.05) in the intensity of yellow color and mango flavor from the line test could have influenced the results of triangle test for difference and paired-preference test. The pH, TA and TSS of F1 were 4.96, 0.25% and 15.92 °Brix whereas F2 obtained 4.87, 0.35% and 12.5 °Brix, respectively. The titratable acidities (%) and total soluble solids of F1 and F2 were found significantly different (T-test at 5% level of significance). F2 had a proximate composition of 73.25% moisture, 13.64% fat, 1.64% protein, 0.79% fiber, 0.85% ash and 9.83% carbohydrates. The product was thick with spreading distance of 4.17 cm/min. Consumer testing revealed that 44% of the respondents liked the product very much and 22% liked it moderately which suggest that the mango-flavored yogurt analogue has a great market potential.